PENGENALAN PEMASARAN DIGITAL DAN LAPORAN KEUANGAN BAGI PELAKU UMKM DI DESA RANCABUNGUR KABUPATEN BOGOR - Farradia, Yuary; Hadi, Delta; Prasetyo, Buntoro Heri; Supriyanto, Joko (Yayasan Education and Social Center, 2024)
Managing business of Micro, Small, and Medium Enterprises (MSMEs) needs to balance between the marketing effort and financial management in term of financial report toward MSMEs sustainability. The MSMEs needs to up grade their marketing effort through implementing various digital marketing programs. On the other side, managing business also needs proper financial report. MSMEs at Rancabungur Village, Bogor District still facing problem on both marketing and financial report. A community service was conducted to improve the skill of MSMEs through introduction program of marketing digital and making a simple financial report. About 20 MSMEs participants joined the workshop to understand the marketing digital and financial report at Rancabungur Village. Trough this workshop, participants were educated the best practice in utilizing various social media in digital marketing and also has introduction practice on creating the simple financial report of their particular business. Further workshop recommendation about creating content on socia media marketing as well as creating the profit and loss statement of the business are needed in future workshop series